Florida's Introduced Birds: Eurasian Collared-Dove (Streptopelia decaocto) - Steve A. Johnson; Gay Donaldson-Fortier (EDIS)
WEC-256, a 5-page illustrated fact sheet by Steve A. Johnson and Gay Donaldson-Fortier, introduces the Eurasian Collared-Dove — species description, similar species, native range and habitats, mode of introduction, introduced range and habitats, ecological impacts, impacts to people and pets, and solutions. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, April 2009.